The venom of Bothrops asper from Guatemala: toxic activities and neutralization by antivenoms - Saravia Otten, Patricia (2001)
Bothrops asper is responsible for approximately half of the snakebite envenomations in Central America. Despite its medical relevance, only the venom of Costa Rican populations of this species has been studied to some detail, and there is very little information on intraspecies variability in venom composition and toxicity. Venom of B. asper from Guatemala was analyzed by sodium dodecyl sulphate–polyacrylamide gel electrophoresis and two-dimensional gel electrophoresis, and its basic pharmacological activities were investigated with standard laboratory assays. Venom has lethal, hemorrhagic, myotoxic, edema-forming, coagulant, defibrinating and phospholipase A2 activities, showing a similar toxicological profile to the one previously described for B. asper from Costa Rica. In addition, polyvalent antivenoms produced in Mexico and Costa Rica, and currently used in Guatemala, were tested for their ability to neutralize venom’s toxic activities. Both antivenoms were effective against all effects studied, although the Costa Rican product showed higher potency against most activities tested and higher antibody titer against venom components, as determined by enzyme immunoassay. It is suggested that different dosage regimes should be considered when using these antivenoms in B. asper envenomations in Guatemala.